2012
DOI: 10.1038/bjc.2012.80
|View full text |Cite
|
Sign up to set email alerts
|

MMP-2 and MMP-9 in normal mucosa are independently associated with outcome of colorectal cancer patients

Abstract: Background:Upregulation of the matrix metalloproteinases MMP-2 and MMP-9 in various cancers has been associated with worse survival of the patients.Methods:We assessed MMP-2 and MMP-9 levels in normal colorectal mucosa from colorectal cancer patients in relation to the course of the disease.Results:A high protein expression of MMP-2 as well as MMP-9 in normal mucosa was found to be correlated with worse 5-year survival. The combination of both parameters was an even stronger prognostic factor. These protein le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
42
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 18 publications
(20 reference statements)
12
42
0
2
Order By: Relevance
“…Much evidence has linked MMPs to aggressive, malignant behavior, and poor outcome in various cancer cells, including prostate cancer, breast cancer, lung cancer et al They remodel the extracellular matrix and increase the invasive potential of tumor cells. The expression level is associated with tumor invasion ability and survival (Quaranta et al, 2007;Chen et al, 2012;Irena et al, 2012;Langers et al, 2012;Dai et al, 2013). Our study showed mIDH1 reduced the invasion ability of glioma cells and was further reduced by TMZ.…”
Section: Discussionsupporting
confidence: 53%
“…Much evidence has linked MMPs to aggressive, malignant behavior, and poor outcome in various cancer cells, including prostate cancer, breast cancer, lung cancer et al They remodel the extracellular matrix and increase the invasive potential of tumor cells. The expression level is associated with tumor invasion ability and survival (Quaranta et al, 2007;Chen et al, 2012;Irena et al, 2012;Langers et al, 2012;Dai et al, 2013). Our study showed mIDH1 reduced the invasion ability of glioma cells and was further reduced by TMZ.…”
Section: Discussionsupporting
confidence: 53%
“…Langers et al (Langers et al, 2012) have found that high expression of MMP-2 and MMP-9 in the mucosa of colon cancer patients is associated with a 5-year mean survival (Grigioni et al, 1994;Sier et al, 1996). In this study, we found similar results regarding MMP-2 and MMP-9 expression in EGISTs, i.e., the expression of MMP-2 and MMP-9 was associated with tumor progression, which is consistent with previous findings (Grigioni et al, 1994;Sier et al, 1996;Zeng et al, 1996;Ring et al, 1997;Yukawa et al, 2001;Zhang et al, 2003;Liu et al, 2010;Langers et al, 2012). However, our current study did not show the underlying molecular mechanisms responsible for upregulation of MMP-2 and MMP-9 in EGISTs or how MMP-2 and MMP-9 proteins promote EGIST progression.…”
Section: Discussionmentioning
confidence: 99%
“…In CRC patients, plasma MMP-2 levels are correlated with disease stage and survival (19), while MMP-9 expression is correlated with the progression of CRC and hence may be a potential target for the treatment of CRC (20,21). Furthermore, MMP-2 and MMP-9 expression in normal mucosa from patients with CRC are independently associated with the outcome of patients with CRC (22). Therefore, to elucidate the mechanism of the antimetastatic effect of baicalein, the present study determined the expression levels of MMP-2/-9 in CRC cells treated with baicalein, and baicalein was demonstrated to significantly inhibit the protein expression levels of MMP-2/-9 in CRC cells.…”
Section: Discussionmentioning
confidence: 99%